2019
DOI: 10.25105/ber.v18i1.5175
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Job Satisfaction and Organization Commitment to Job Performance Through Organizational Citizenship Behavior (Ocb) as Meditation Variable (Empiris Study on Pt. Bank Mandiri at Jakarta)

Abstract: <p><em>Global competition requires organization to adapt to the ever-rapidly changing ways to do business in the global environment in order to keep survive. The success of the organization does not only depend on facility and infrastructure that is available but also on their employes performance. Therefore, an organization needs to realize how important the role of their employes for the triumph of the organization.</em></p><p><em> </em></p><p><em>T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
(3 reference statements)
3
4
1
2
Order By: Relevance
“…In summary, our findings are substantially in line with evidence that more satisfied workers show higher in-role (e.g., TP) and extra-role performance (e.g., OCB) [ 9 , 12 , 13 , 16 , 17 , 29 , 30 , 31 ]. The novelty of our study is that OCB partially mediates the effect of JS on TP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In summary, our findings are substantially in line with evidence that more satisfied workers show higher in-role (e.g., TP) and extra-role performance (e.g., OCB) [ 9 , 12 , 13 , 16 , 17 , 29 , 30 , 31 ]. The novelty of our study is that OCB partially mediates the effect of JS on TP.…”
Section: Discussionsupporting
confidence: 90%
“…Thus far, however, only a few studies have considered the three dimensions simultaneously within a mediation model. Indeed, two studies found that JS had significant positive effects on TP using OCB as an intervening variable [ 30 , 31 ] but results were not reported in terms of total or partial mediation.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are in accordance with the results of Putri & Suwandana (2016) which proves that there is a relationship between the significant positive influence of transformational leadership style and compensation on Organizational Citizen Behavior (OCB) in the Bina Sejahtera Civil Servant Cooperative, Badung Regency. This is also in line with the research by Setiawan & Gunawan (2019) which describes the strength of the relationship between transformational leadership (X1) and Organizational Citizenship Behavior (Y) indicated by the correlation coefficient ry1 = 0.603 and contributes 36.4% to Organizational Citizenship Behavior.…”
Section: Table 4 Description Of Loyalty Data (X 3 )supporting
confidence: 91%
“…There are two leadership styles, namely transactional leadership and transformational leadership (Lussier & Achua, 2016) Previous research has shown that transformational leadership greatly influences the development of OCB attitudes in employees. Setiawan & Gunawan (2019) stated in their research that there is a significant positive relationship between transformational leadership style and compensation on Organizational Citizen Behavior (OCB). Setiawan & Gunawan's research (2019) shows that transformational leadership contributes 36.4% to Organizational Citizenship Behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Satisfied employees are usually happy and motivated to do their job, and they perform better (Miah, 2018). Meanwhile, dissatisfied employees usually do not try their best and fail to do their job at an optimal level (Setiawan & Gunawan, 2018). Organizational commitment is identified as one of the key factors that influence employee job satisfaction (Culibrk, Delic, Mitrovic & Culibrk 2018).…”
Section: Introductionmentioning
confidence: 99%